A Systematic Review of the Benefits of Mindfulness-Based Interventions following Transient Ischemic Attack and Stroke. Issue 6 (August 2013) - Lawrence, Maggie; Booth, Jo; Mercer, Stewart; Crawford, Elizabeth
Background: Recent epidemiological studies have demonstrated an association between perceived psychological stress and ischemic stroke. A feature of stroke is recurrence; 30–40% within five-years following first transient ischemic attack/stroke. Equipping patients with skills and coping strategies to help reduce or manage perceived psychological stress may represent an important secondary prevention intervention. Mindfulness-based interventions are structured, group-based self-management programmes with potential to help people with long-term conditions cope better with physical, psychological, or emotional distress. Review evidence suggests significant benefits across a range of physical and mental health problems. However, we could find no evidence synthesis relating specifically to the benefits of mindfulness-based interventions following transient ischemic attack/stroke. Aim: The review aims to evaluate the benefits of mindfulness-based interventions following transient ischemic attack/stroke. Methods: Six major databases were searched using subject headings and key words. Papers were screened using review-specific criteria. Critical appraisal and data extraction were conducted independently by two reviewers. Statistical meta-analysis was not possible; therefore findings are presented in narrative form. Results: Four studies involving 160 participants were reviewed. Three papers reported mindfulness-based interventions delivered to groups; one paper reported a mindfulness-based intervention which was delivered one to one. The results demonstrate a positive trend in favor of the benefits of mindfulness-based interventions across a range of psychological, physiological, and psychosocial outcomes including anxiety, depression, mental fatigue, blood pressure, perceived health, and quality of life. No evidence of harm was found. Conclusion: Following transient ischemic attack/stroke, people may derive a range of benefits from mindfulness-based interventions; however, further methodologically robust trials are required.